An Atypical HNF4A Mutation Which Does Not Conform to the Classic Presentation of HNF4A-MODY - Andrew J. Spiro; Katherine N. Vu; Alicia Lynn Warnock (Case Reports in Endocrinology)
Objective. To present the case of an atypical Hepatocyte Nuclear Factor 4 Alpha (HNF4A) mutation that is not consistent with the classically published presentation of HNF4A-Mature Onset Diabetes of the Young (MODY). Methods. Clinical presentation and literature review. Results. A 43-year-old nonobese man was referred to the endocrinology clinic for evaluation of elevated fasting blood glucose (FBG) measurements. Laboratory review revealed prediabetes and hypertriglyceridemia for the previous decade. Testing of autoantibodies for type 1 diabetes was negative. Genetic testing showed an autosomal dominant, heterozygous missense mutation (c.991C>T; p.Arg331Cys) in the HNF4A gene, which is correlated with HNF4A-MODY. Phenotypically, patients with an HNF4A-MODY tend to have early-onset diabetes, microvascular complications, low triglyceride levels, increased birth weight, fetal macrosomia, and less commonly neonatal hyperinsulinemic hypoglycemia. The patient did not demonstrate any of these features but instead presented with late-onset diabetes, an elevated triglyceride level, and a normal birth weight. Conclusion. Our patient likely represents an atypical variant of HNF4A-MODY with a milder clinical presentation. Patients with atypical, less-severe presentations of HNF4A-MODY may be largely undiagnosed or misdiagnosed, but identification is important due to implications for treatment, pregnancy, and screening of family members.